Direct transesterification to produce bio-diesel from Oedogonium algae and duckweed plant - Wed Al-Graiti; Asaad H. Sayer; Saleem Ethaib; Sameerah Jameel Tarfa; Amina Sabah Hashem (Caspian Journal of Environmental Sciences)
Biodiesel from renewable sources is one of the possible alternatives support the energy security. This study aimed to produce biodiesel from Oedogonium algae and duckweed plant by direct transesterification. An amount of 5 g of dry biomass was taken for the considered duckweed plant and the algae was immersed in 50 mL of methanol: hydrochloric acid: chloroform (10:1:1 v/v/v)   solvent to extract fatty acid methyl esters (FAME).  The extracted materials were taken for the characterisation using FT-IR and GC-Mass spectrometry. The prepared samples were specifically diagnosed for the identification of compounds particularly lipids. The results showed presence of saturated and unsaturated fatty acids in the formed ester (biodiesel). Saturated and unsaturated fatty acids identified in the biodiesel derived from duckweed plant were 24.19% and 20.34% respectively and from Oedogonium algae were 19.92% and 17.2% respectively. These results demonstrated a high potential to produce biodiesel from these types of biomass which could provide another route for energy supply.